STUDY OF PONDERAL INDEX IN FRESHWATER FISHES WALLAGO ATTU (SCHNEIDER) AND NOTOPTERUS NOTOPTERUS (HAMILTON) - SHENDGE, A.N.; MANE, U.H. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Wallago attu and iVotopterus noloplerus, the common freshwater catfishes of Bhima river, have high economic and considerable fishery importance. The variations in the ponderal index in respect to size groups. maturation, spawning and feeding intensity have been studied. The work was carried out on 224 specimens of Wallago al/ii ranging from 21.00 to 34.90cms and 164 specimens of Nolopterus notopterus ranging from 21.00 to 32.90cms in length. N. notopterus showed comparatively high value of K (0.8712) than W. a/u (0.5653), suggesting well being of N. notopt crus than W. attu.